The Effect of Market and Entrepreneurial Orientation, Product Quality on the Competitive Advantage of Batik MSMEs in Yogyakarta - Putra, Adhitya Wisaka; Nuvriasari, Audita (LifeSciFi, 2024)
This study aims to analyze the Influence of Market Orientation, Entrepreneurial Orientation and Product Quality on the Competitive Advantage of Batik MSMEs in the Special Region of Yogyakarta. The research sample was 45 people in charge or owners of MSMEs determined using purposive sampling techniques. The data analysis tool used was multiple linear regression analysis. The results of this study prove that Market orientation does not have a significant effect on the Competitive Advantage of Batik MSMEs in the Special Region of Yogyakarta. Entrepreneurial Orientation does not have a significant effect on the Competitive Advantage of Batik MSMEs in the Special Region of Yogyakarta. Product Quality has a positive and significant effect on the Competitive Advantage of Batik MSMEs in the Special Region of Yogyakarta. The findings of this study indicate that market orientation is not a determining factor in competitive advantage. Entrepreneurial orientation does not have a significant effect on the competitive advantage of Batik MSMEs in the Special Region of Yogyakarta. The findings of this study indicate that entrepreneurial orientation is not a determining factor in competitive advantage. Product quality has a positive and significant effect on the competitive advantage of Batik MSMEs in the Special Region of Yogyakarta.